Dyskeratosis Congenita and Squamous Cell Cancer of the Head and Neck: A Case Report and Systematic Review. (September 2022) - Liu, Alice Q.; Deane, Emily C.; Prisman, Eitan; Durham, J. Scott
Objectives: Dyskeratosis congenita (DC) is a progressive congenital disorder that predisposes patients to squamous cell cancers (SCC) of the head and neck. We report a case of a patient who underwent primary osteocutaneous free flap for mandibular SCC followed by additional treatments for positive margins and discuss a systematic review on therapeutic management for this patient population. Methods: Case report of a 39-year-old male with DC who underwent resection and reconstruction with a fibular free flap for mandible SCC, followed by revision surgery and adjuvant radiotherapy for positive margins. A systematic review was completed afterward with the following terms: "dyskeratosis congenita" AND "oral cancer" OR "head and neck" OR "otolaryngology" on Medline and Web of Science for articles between 1980 and 2021. In total, 12 articles were included that reported on DC and SCC in the head and neck. Results: Of the case reports that were included in this review, half the patients had recurrence within 1 year of primary treatments. Only 2 patients did not require revision surgery, adjuvant, or salvage therapy. Half of patients that received radiation therapy had severe side effects. Conclusions: This is the largest review of DC and SCC in the head and neck. Based off our case report and review, these patients have aggressive disease that often requires multi-modality treatment. Consideration should be taken in regards to reports of side effects with radiation therapy.